1994
DOI: 10.1083/jcb.125.3.695
|View full text |Cite
|
Sign up to set email alerts
|

Cell-specific expression of alpha 1(I) collagen-hGH minigenes in transgenic mice.

Abstract: Abstract. Sequences within the first intron of the od(I) collagen gene have been implicated in the regulation of expression of .l(I) collagen-reporter gene constructs in cultured cells. However, the physiological significance of these intronic elements has not been established. We have used in situ hybridization to examine whether a cell-specific pattern of expression of human oel (I) collagen-human growth hormone minigenes exists in transgenic mice. Our results indicate that transgenes which contained 2,300 b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
60
3

Year Published

1995
1995
2005
2005

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 69 publications
(68 citation statements)
references
References 39 publications
5
60
3
Order By: Relevance
“…In the above model, these sequences are assumed not to interact with the ACH, as they belong to a different functional transcription unit and can consequently synergize with local promoters. Consistent with this suggestion, unpublished work 3 has shown that the short intergenic region between Emilin1 and Khk contains an activating sequence for Khk that is located within the 16.8-kb fragment studied here.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…In the above model, these sequences are assumed not to interact with the ACH, as they belong to a different functional transcription unit and can consequently synergize with local promoters. Consistent with this suggestion, unpublished work 3 has shown that the short intergenic region between Emilin1 and Khk contains an activating sequence for Khk that is located within the 16.8-kb fragment studied here.…”
Section: Discussionsupporting
confidence: 70%
“…gated the regulatory sequences responsible for tissue-specific expression of ECM genes (1)(2)(3)(4)(5)(6). The overall picture coming from these studies is a modular arrangement of regulatory regions (mostly enhancers), meaning that each region is a distinct and independent regulator of transcription in a specific tissue or in a set of tissues.…”
mentioning
confidence: 99%
“…9 B), since collagen gene expression in dermal fibroblasts has been shown to require the first intron (23). However, expression of the -1627 COL-/3-galactosidase transgene was readily detected in tendon, indicating that the first intron is not required for collagen a I(I) gene expression in tendon fibroblasts (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The comparable values for the -440 COL-hGH and -2300 COL-hGH mRNAs in day 10 stellate cells, were 40.3 and 106, respectively. The variable baseline expression of the transgenes is related to copy number and "leakiness" of the construct, and it is therefore less informative than the increase in expression following activation, as described previously (23 CCAAT binding proteins are thought to be important in the regulation of the collagen a I(I) gene because in human, rat, and mouse two highly conserved CCAAT binding sequences are present in the collagen a I(I) promoter sequence ( 19). CBF is a CCAAT binding factor isolated from liver nuclear extracts which binds to both CCAAT sites (38).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation